2005
DOI: 10.1007/s00221-005-0091-1
|View full text |Cite
|
Sign up to set email alerts
|

Switching, plasticity, and prediction in a saccadic task-switch paradigm

Abstract: Several cognitive processes are involved in task-switching. Using a prosaccade/antisaccade paradigm, we manipulated both the interval available for preparation between the cue and the target and the predictability of trial sequences, to isolate the contributions of foreknowledge, an active switching (reconfiguration) process, and passive inhibitory effects persisting from the prior trial. We tested 15 subjects with both a random and a regularly alternating trial sequence. Half of the trials had a short cue-tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
63
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 25 publications
12
63
1
Order By: Relevance
“…Another possibility is that one might not know which stimulus will appear, but know the type of response that will be required. In the saccadic paradigm, one may then be uncertain as to which side the target would appear, but know from the trial sequence that an antisaccade was the required response (Barton et al, 2005;Sohn and Anderson, 2001;Tornay and Milan, 2001). This would be a 'set-foreknowledge.'…”
Section: Varieties Of Foreknowledgementioning
confidence: 99%
See 2 more Smart Citations
“…Another possibility is that one might not know which stimulus will appear, but know the type of response that will be required. In the saccadic paradigm, one may then be uncertain as to which side the target would appear, but know from the trial sequence that an antisaccade was the required response (Barton et al, 2005;Sohn and Anderson, 2001;Tornay and Milan, 2001). This would be a 'set-foreknowledge.'…”
Section: Varieties Of Foreknowledgementioning
confidence: 99%
“…Our recent investigations have focused on the benefits of set foreknowledge in a saccadic paradigm (Barton et al, 2005). Set-foreknowledge in particular is revealed during instances where the set changes from one trial to the next.…”
Section: Experiments In Set Foreknowledge: Does Prediction Always Help?mentioning
confidence: 99%
See 1 more Smart Citation
“…In a Stroop paradigm in which subjects switch between automatic word reading and controlled color naming tasks, a greater switch cost is observed on a word-reading trial after color naming than on a color-naming trial after word reading (Allport et al, 1994). Also, when switching between prosaccade and controlled antisaccade, that is, when switching between rules to make a saccade to and away from a visual target, a greater switch cost is observed on a prosaccade trial that follows an antisaccade trial than on an antisaccade trial that follows a prosaccade trial (Cherkasova et al, 2002;Fecteau et al, 2004;Barton et al, 2006). Moreover, responses become faster when switching from prosaccade to antisaccade than when repeating antisaccade.…”
Section: Introductionmentioning
confidence: 99%
“…These results cannot be accounted for by the extra neural processing to establish the rule representation for controlled behavior, as this would result in an increase in RTs when switching from automatic to controlled behavior rather than vice versa. It is also shown that the effect cannot be eliminated with ample task preparation time of several seconds (Allport et al, 1994;Rogers and Monsell, 1995;Meiran, 2000;Barton et al, 2006), suggesting that a mechanism involved in the aftereffect of controlled behavior cannot be updated during a task preparation period on the next trial.…”
Section: Introductionmentioning
confidence: 99%